STRATEGI PENGEMBANGAN USAHA BATU BATA DI DESA KOTA AGUNG KECAMATAN AIR BESI KABUPATEN BENGKULU UTARA - -, Karnadi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2016)
The development of the industrial sector should be developed to encourage economic activity, especially in sectors that support the activities of entrepreneurship .To develop the industrial sector can be done by identifying the factors that support the factors of strengths, weaknesses, opportunities, and challenges faced in the development of a brick.Brick is a business venture that has been known by the public, especially by the people of Bengkulu Utara. Excellence of the qualities of this brick making business has the potential to be further developed, but the problem is that these efforts have not managed optimally by managers and local governments. Strategy formulation is done by using SWOT analysis. Results of this study showed that of the SWOT analysis, which uses matrix EFAS, IFAS, and SWOT matrix. External factors with the highest scores that affect business development opportunities bricks are factors that settlement growth opportunities, while the highest threat is the increasing internal competition.Internal factors with the highest score is the strength factor that is of good quality, while the highest weakness is the lack of knowledge on the technology and quality control due to the lack of opportunity to keep abreast of times. Next is the formulation of the proposed development strategy is based on a fundamental strategy in the strategy of strength and opportunities, strategies, weaknesses and opportunities, strengths and threats strategy, and strategy weaknesses and threats. Keywords: Industry, SWOT analysis, Bricks Business Village City Court